Keaktifan dan Hasil Belajar Siswa Materi Denah dengan PBL Kelas III SD - Yunila Dwi Kumalasari; Maria Melani Ika Susanti; Maria Indarti Rustamti (Program Studi PGSD STKIP PGRI Banjarmasin, 2022)
The purpose of this study was to increase the students activeness and students learning outcomes for elementary school with the Problem Based Learning model. This research is Classroom Action Research (CAR) which was conducted in two cycles. The subjects of this study were the third grade students of SDN Tambahmulyo 02 as many as 20 students. The object of this research is student activiteness and student learning outcomes in Bahasa Indonesia lesson. The data collection by observation and test, while the data analyzed with quantitative descriptive. This test is used to determine the level of students activitiness and students learning outcomes. The result for first cycle was 60% increased to 80% for second cycle. Student learning outcomes for first cycle was 69 increased to 84.5 for the second cycle. The results showed that the Problem Based Learning model could increase of students activeness and students learning outcomes for the third grade students of SDN Tambahmulyo 02.